BEBERAPA FAKTOR TERJADINYA TINDAK PENCABULAN OLEH ANAK (Studi pada Kepolisian Resort Banggai) - H.M. Ikhwan Rays (Jurnal Yustisiabel, 2020)
This research is intended to study what factors are causing the follow-up of child molestation in Banggai Regency and what efforts have been made by the Banggai Resort Police in an effort to overcome the crime of sexual abuse by children in the District. Be proud To find out the objectives needed, this study uses empirical juridical where the method or method used in this legal research is to use primary data, that is the data obtained by the author from the research location and use secondary data obtained from data / existing library materials. Outcome factors, factors that cause child abuse in Banggai Regency are: educational factors, environmental factors, alcoholic drinks factors and technological factors. Whereas the efforts carried out by the Banggai Regional Police consist of: pre-emptive efforts, preventive measures and repressive efforts